In-vitro Bactericidal Kinetics of Chlorhexidine Gluconate Disinfectant/ Antiseptic Formulations Containing Different Additives (2014)
Chlorhexidine gluconate(CHG) is a popular disinfectant/antiseptic which is often formulated with additives. We investigated the effect of additives type on the in vitro bactericidal kinetics of CHG in three commercially available formulations: Hibiscrub®, Savlon® and Purit® commonly used as household and hospital disinfectants/antiseptics. The bactericidal kinetics of the products was determined by time-survival curve method using Pseudomonas aeruginosa NCTC 6750 and Staphylococcus aureus NCTC 6571 as model organisms. Best-fit rate constant and half-life was computed by exponential decay curve-fitting. Half-life was; 76.5, 65.5, 66 and 74 (min) for Control solution, Hibiscrub®, Savlon® and Purit® respectively, against Ps. aeruginosa. The corresponding values obtained against Staph. aureus are 51.0, 61.7, 29.3, and 49.0 (min) (95% CI). Presence of alcohol (e.g. Hibiscrub® and Savlon®) caused an insignificant increase in the rate of killing of Ps. aeruginosa relative to preparations that are devoid of alcohol. (p>0.05, 1-way ANOVA). Toward Staphylococcus aureus, the combined effect of cetrimide and alcohol (e.g. Savlon®) is higher than any enhancement due to combination of alcohol and surfactant (e.g. Hibiscrub). Savlon® show a significantly higher bactericidal effect of all the preparations (P<0.0001, 1-way ANOVA). The choice of additives in the formulation of chlorhexidine antiseptic solutions significantly alters the kinetics and overall bactericidal effect of CHG towards Staphylococcus aureus but not Pseudomonas areruginosa.